Film Properties, Water Retention, and Growth Promotion of Derivative Carboxymethyl Cellulose Materials from Cotton Straw - Yongni Wu; Mengfan Yu; Yanju Li; Yue Wu; Ziqiang Shao; Yanhua Liu (Advances in Polymer Technology)
Three kinds of derivative carboxymethyl cellulose (DCMC) materials, CMC-Na, CMC-K, and CMC-NH4, were prepared from cotton straw fiber. Their chemical structure, film morphology, water retention, biodegradability, and growth promotion were investigated with infrared spectroscopy (IR), scanning electron microscope (SEM), and field experiments. The results showed that the infrared absorption peaks of the three materials were similar. It was observed that the DCMC materials could form films after being sprayed at the amount of 4.00 g/m2 and 12.00 g/m2, and the film thickness was showed in the order of CMC-K, CMC-NH4, and CMC-Na. The largest water holding capacity increased significantly after DCMC was sprayed on the soil. The water retention of CMC-Na, CMC-K, and CMC-NH4 increased by 47.74%, 72.85%, and 61.40% severally while sprayed with 12.00 g/m2 compared to the control group (CK), and the water retention rate increased with 6.93, 9.75, and 8.67 times, respectively, on the seventh day. The total number of soil microorganisms increased with the DCMC materials being sprayed; the number in the upper layer increased by 92.31%, 123.08%, and 138.46%, respectively, compared with CK. When the three materials were used to the cornfield at the amount of 100.00 kg/hm2, the corn yield increased by 33.11%, 70.93%, and 50.60%, respectively. The DCMC materials, as the sole carbon source, could be degraded by soil microorganisms. The nutrient elements such as NH4+ in the materials could further promote the growth of microorganisms and crops. This study might provide a new way to apply straw-based DCMC in soil water retention, soil amendment, and high value-added transformation of straws in arid areas.